2022
DOI: 10.1007/s40291-022-00596-0
|View full text |Cite
|
Sign up to set email alerts
|

Immune-Checkpoint Expression on CD4, CD8 and NK Cells in Blood, Bronchoalveolar Lavage and Lymph Nodes of Sarcoidosis

Abstract: Background Sarcoidosis features non-necrotizing granulomas consisting mainly of activated CD4-lymphocytes. T-cell activation is regulated by immune checkpoint (IC) molecules. The present study aimed to compare IC expression on CD4, CD8 and NK cells from peripheral, alveolar and lung-draining lymph node (LLN) samples of sarcoidosis patients. Methods Flow-cytometry analysis was performed to detect IC molecules and a regression decision tree model was constructed to investigate potential binary classifiers for sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
3
6
0
Order By: Relevance
“…This eventually leads to their migration to inflammatory foci and the formation of granulomas [ 20 ]. The present study confirmed data in the literature on depletion of CD56 dim 16 bright and CD8 + T cells in LLN and BAL samples with respect to PB, suggesting that these cells play a protective role in sarcoidosis [ 5 , 17 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This eventually leads to their migration to inflammatory foci and the formation of granulomas [ 20 ]. The present study confirmed data in the literature on depletion of CD56 dim 16 bright and CD8 + T cells in LLN and BAL samples with respect to PB, suggesting that these cells play a protective role in sarcoidosis [ 5 , 17 ].…”
Section: Discussionsupporting
confidence: 91%
“…Sarcoid lung involvement can be evaluated by flexible bronchoscopy with bronchoalveolar lavage (BAL), cytological analysis and evaluation of T cell expression, typically characterized by an increase in alveolar lymphocytes having an elevated CD4/CD8 ratio [ 4 ]. For better diagnostic accuracy, it is advisable to perform endobronchial ultrasound-transbronchial needle aspiration (EBUS-TBNA) during flexible bronchoscopy, a minimally invasive technique that allows sampling of lung-draining lymph nodes (LLNs) for cytological analysis [ 5 , 6 ]. This procedure has been widely adopted and is currently recommended by international guidelines as the gold standard for evaluating intrathoracic lymphadenopathy in cases of suspected sarcoidosis [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…13,15 Programmed cell death 1 (PD-1), cytotoxic Tlymphocyte antigen 4 (CTLA-4) and lymphocyte activation gene 3 (LAG-3) are inhibitory receptors associated with the exhaustion phenotype of T cell. 16 Recently, T immunoreceptor with immunoglobulin and ITIM domain (TIGIT), a new molecules with immunoregulatory properties, has been discovered. It is considered a promising new target for cancer immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…While there is limited data on PD-1 + T cells in lung cancer, there is even less knowledge regarding PD-1 expression on T cells in patients with benign lung diseases. d'Alessandro and colleagues reported a high expression of PD-1 on T cells in BAL of patients with sarcoidosis [ 12 ]. Kronborg-White et al described an expression of PD-L1 in epithelial cells in a subgroup of patients with IPF [ 13 ].…”
Section: Introductionmentioning
confidence: 99%